TWO-LINK FLEXIBLE MANIPULATOR AS AN ALTERNATIVE IN IMPROVING ENERGY EFFICIENCY OF MANIPULATOR ROBOT - Moh Khairudin (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2015)
The dynamic model and characterization of a two-link ﬂ exible manipulator as an alternative for manipulator robot to achieve the efﬁ ciency on consuming electrical energy comparing with rigid manipulator. A planar two-link ﬂ exible manipulator was combined with structural damping, hub inertia and payload that moving horizontally. A dynamic model system was developed using the combination of Euler-Lagrange and assumed mode methods. Armed with the developed model, then some simulations were done to examine the dynamic model and the response of the system on the hub and the end point of both link that were presented and analyzed in function of time and frequency. The results show that the bang-bang input of 0.15 volt can move the link 1 on 55 0 and link-2 on 122 respectively. It means that the dynamic model uses more efﬁ cient energy compared with rigid manipulator robot which required bigger input for moving.